2016
DOI: 10.1007/978-3-319-32360-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Characterization of the Uniqueness Regions Under Special Sets of Three Directions in Discrete Tomography

Abstract: The faithful reconstruction of an unknown object from projections, i.e., from measurements of its density function along a finite set of discrete directions, is a challenging task. Some theoretical results prevent, in general, both to perform the reconstruction sufficiently fast, and, even worse, to be sure to obtain, as output, the unknown starting object. In order to reduce the number of possible solutions, one tries to exploit some a priori knowledge. In the present paper we assume to know the size of a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In 2015 Dulio, Frosini and Pagani [6] showed that in the corners of A the function values are uniquely determined and can be computed in linear time if the number of directions d = 2. Later they proved conditional results for d = 3 [7,8]. Recently, Pagani and Tijdeman [19] generalized the result for any number of directions.…”
Section: Introductionmentioning
confidence: 93%
“…In 2015 Dulio, Frosini and Pagani [6] showed that in the corners of A the function values are uniquely determined and can be computed in linear time if the number of directions d = 2. Later they proved conditional results for d = 3 [7,8]. Recently, Pagani and Tijdeman [19] generalized the result for any number of directions.…”
Section: Introductionmentioning
confidence: 93%
“…They also showed that the problem is NP-complete for d ≥ 2 when the function contains six or more different values. In 2015 Dulio, Frosini and Pagani proved that the corners of A can be uniquely determined in linear time for d = 2 [3], and gave conditional results for d = 3 [4,5]. This result was generalised by Pagani and Tijdeman for any number of directions [11].…”
Section: Introductionmentioning
confidence: 95%
“…The switching function is elementary. By (4) we have T = {(0, 2, 2), (1, 0, 3), (1, 2, 2), (1, 3, 0), (1,3,4), (2, 0, 3), (2, 1, 1), (2, 1, 5), (2, 3, 0), (2,3,4), (2, 4, 2), (3, 1, 1), (3, 1, 5), (3, 2, 3), (3, 4, 2), (4, 2, 3)} .…”
Section: Example 4 Let Be Givenmentioning
confidence: 99%
“…In general, the number of matrices sharing the same projections grows exponentially with their dimension, so in most practical applications some extra information are needed to achieve a solution as close as possible to a starting unknown object. So, researchers tackle the algorithmic challenges of limiting the class of possible solutions in different ways: increasing the number of projections (Gardner and Gritzmann 1997;Gardner et al 1999), fixing the wideness of the unknown object (Dulio et al 2015(Dulio et al , 2016(Dulio et al , 2017b or adding geometrical information (mainly connectedness and convexity). Concerning this last, among connected sets a dominant role deserved polyominoes, that are commonly intended as finite 4-connected sets of points of the integer lattice, considered up to translation.…”
Section: Introductionmentioning
confidence: 99%